Pengaruh Promosi Dan User Experience Terhadap Kepuasaan Yang Berdampak Pada Loyalitas Supplier Pada Situs E-Commerce Tokodistributor - Guna, Darma; Meliana, Vina (Research and Community Service UNIVERSITAS KALBIS, 2024)
This study aims to determine the effect of promotion and user experience (ux) on satisfaction which has an impact on supplier loyalty on distributor store e-commerce sites. This study uses a quantitative research method with a purposive sampling technique in collecting questionnaire data, the researcher uses a sample of suppliers who are actively selling on e-commerce sites which 130 users of distributor shops. The results of this study indicate that promotion has an effect on satisfaction user experience has no effect on satisfaction. and there is no effect of satisfaction on loyalty. Promotion and user experience were found to have a joint effect on satisfaction.